Self-Reported Halitosis and Associated Factors Among Medical and Dental Students of a Tertiary Institution in Rivers State, Nigeria - Grace Alade; CF Ezebunwa (Nigerian Dental Association, 2023)
Objectives: To determine the prevalence of self-reported halitosis and associated factors among medical and dental students of the university of Port Harcourt.  Material and Methods: This was a cross-sectional study, conducted among medical and dental undergraduate students of the University of Port-Harcourt (UPH), Rivers State. Consent was obtained from each participant before being enrolled into the study. Data was collected using a self-administered structured questionnaire. The questionnaire was grouped into four (4) sections; Section A collected demographical information (gender, age, course and level), section B collected information on self-reported halitosis and self-care, section C collected information on oral hygiene practices and section D collected information on associated factors. Data collected was analysed using the IBM Statistical Package for Social Sciences (SPSS) version 27 (IBM SPSS Armonk, New York) software for Windows. Categorical variables were expressed as frequencies with accompanying percentages. Differences between groups were compared using the Chi-square tests for categorical variables. All statistical significances were assumed at p values <0.05. Results: A total of 248 medical and dental students were recruited as study participants. The age range was 15-30 years, with a mean age of 22.9 years.  The male-to-female ratio is 1.13:1. The prevalence of self-reported halitosis among the study participants was 26%, with the worse experience being in the morning (31.1%). The younger age group reported more halitosis compared to the older age group (p=0.016). More females (34.5%) significantly reported halitosis compared to males (18.2%) [p=0.003]. The occurrence of self-reported halitosis also decreases with an increase in the level of study (p=0.003). Participants that brush thrice a day, and do not use toothbrushes and toothpaste, claim to have halitosis. The majority of the participants who claimed to have dry mouth (76.5%), coated tongue (80.6%) and have a history of smoking (58.3%), reported the presence of halitosis. The majority of participants who take alcohol, claimed not to have halitosis however, this finding is not statistically significant.   Seventy-three (29.4%) of the respondents instituted self-care for halitosis in the form of chewing gums (13.71%), minty candy (8.06%), mouth-washes (6.45%), while 1.21% use other options such as compulsive toothbrushing. Conclusion: Self-reported halitosis was found among 26% of participants. Halitosis occurred more in females and was significantly associated with dry mouth, coated tongue and smoking. 29.4% of the participants instituted self-care to mask their halitosis.